1984
DOI: 10.1577/1548-8659(1984)4<514:roynpt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Young-of-the-Year Northern Pike to Aquatic Vegetation Types in Backwaters of the Upper Mississippi River

Abstract: The association of young-of-the-year northern pike (Esox lucius) with different aquatic plant types (e.g., submerged, emergent, floating) was studied to evaluate the impacts of a potential loss of backwaters on available fish nursery habitats in the upper Mississippi River. Eight biweekly collections were made at each of six representative !entic habitats in Navigation Pool 7. In the spring, average catches of northern pike from areas with submerged vegetation were nearly three times greater than from areas wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 0 publications
2
34
1
Order By: Relevance
“…Fish species composition, diversity and density in the different habitats were found to be different (Gaudreau et al, 1998;Jackson et al, 2001). Vegetation cover and water depth are two of the most important factors influencing spatial distribution of fish (Holland et al, 1984;Hosn et al, 1994). The present study showed that vegetation cover had significant effects on distribution of small fishes in the Xiaosihai Lake (Table 5).…”
Section: Discussionmentioning
confidence: 54%
“…Fish species composition, diversity and density in the different habitats were found to be different (Gaudreau et al, 1998;Jackson et al, 2001). Vegetation cover and water depth are two of the most important factors influencing spatial distribution of fish (Holland et al, 1984;Hosn et al, 1994). The present study showed that vegetation cover had significant effects on distribution of small fishes in the Xiaosihai Lake (Table 5).…”
Section: Discussionmentioning
confidence: 54%
“…several hours). Thus, temporal variations in resource availability and fish feeding activity can account for the mismatch between feeding and growth (Helfman 1978, Holland & Huston 1984, Turner & Mittelbach 1990, Persson 1993. Diurnal pattern of feeding activity of the four species has no not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Lower pike fry abundance is likely a result of a lack of flooded riparian and littoral vegetation (as a result of the fire) used for spawning substrate and cover, and possibly due to a combination of increased cannibalism, reduced quality and quantity of food supply (Figure 2c). Research conducted in the upper Mississippi River, USA, found that catches of Y-O-Y Northern Pike were 10 times greater in vegetated areas compared to non-vegetated areas (Holland and Huston 1984). Dense flooded terrestrial vegetation provides cover and ambush opportunities for Northern Pike fry and keeps them spatially separated from each other, while preventing access by larger Northern Pike that may feed on them (Inskip 1982;Raat 1988).…”
Section: Discussionmentioning
confidence: 99%